2013
DOI: 10.1093/annonc/mdt027
|View full text |Cite
|
Sign up to set email alerts
|

Experience in daily practice with ipilimumab for the treatment of patients with metastatic melanoma: an early increase in lymphocyte and eosinophil counts is associated with improved survival

Abstract: Ipilimumab toxic effect is manageable in real life. Biological data such as lymphocyte and eosinophil counts at the time of the second ipilimumab infusion appear to be early markers associated with better OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
192
4
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(222 citation statements)
references
References 21 publications
23
192
4
3
Order By: Relevance
“…Combination chemotherapies were shown to reduce peripheral lymphocyte count in cancer patients. These findings suggest that treatment-induced lymphopenia may be associated with an increased tumor response (17). In our study, we demonstrated that patients with PLR >200 and eosinophil count <70x10 3 /mm 3 exhibited better DFS rates.…”
Section: Discussionsupporting
confidence: 57%
“…Combination chemotherapies were shown to reduce peripheral lymphocyte count in cancer patients. These findings suggest that treatment-induced lymphopenia may be associated with an increased tumor response (17). In our study, we demonstrated that patients with PLR >200 and eosinophil count <70x10 3 /mm 3 exhibited better DFS rates.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, low LDH serum levels were associated with an increased OS [4,5]. In smaller cohorts treated with ipilimumab reported by Wilgenhof et al [57] and Delyon et al [17], the elevated LDH level was also negatively associated with survival. Moreover, a recent report analyzing several prognostic parameters in two European MM cohorts treated with 3 mg/kg of ipilimumab concluded that an LDH level of > 2 folds above the normal range correlated with clinical failure of CTLA4 blockade [58].…”
Section: -Test) (F)mentioning
confidence: 92%
“…In MM patients, ipilimumab treatment increased the absolute lymphocyte count [17] and the frequencies of circulating HLA-DR + or ICOS + T cells [18,19]. An increase in the absolute eosinophil count has also been associated to clinical benefit [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our data reinforce previous results from clinical trials involving either ipilimumab at a higher dose or another CTLA-4 abrogating antibody, tremelimumab. 21,22,23,38 Prior to treatment, patients' circulating T cells displayed a phenotype compatible with a chronic activation by the tumor, with a lower expression of the costimulatory molecule CD28 and increased percentage of HLA-DR and granzyme B positive CD8 C T cells, when compared to HD. In addition, although not significant, a trend toward higher percentages of TCD8 C T cells expressing CTLA-4 by was also observed, suggesting a post-activation status of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased absolute lymphocyte count (ALC) during the therapy is found to be associated with clinical benefit and overall survival (OS) in uncontrolled studies. 21,22,23,24 In a clinical trial using tremelimumab, another humanized anti-CTLA-4, increased levels of memory and activated T cells were reported in 3 out of 12 patients achieving disease control (DC). 25 Several reports demonstrate immunological changes under ipilimumab therapy, shedding light on in vivo mechanisms of anti-CTLA-4, but their pertinence to predict clinical responses and OS remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%